The Cambridge companion to Machiavelli - Najemy, John M. (Cambridge companions to authors, 2010)
"Niccolo Machiavelli (1469-1527) is the most famous and controversial figure in the history of political thought and one of the iconic names of the Renaissance. The Cambridge Companion to Machiavelli brings together sixteen original essays by leading experts, covering his life, his career in Florentine government, his reaction to the dramatic changes that affected Florence and Italy in his lifetime, and the most prominent themes of his thought, including the founding, evolution, and corruption of republics and principalities, class conflict, liberty, arms, religion, ethics, rhetoric, gender, and the Renaissance dialogue with antiquity. In his own time Machiavelli was recognized as an original thinker who provocatively challenged conventional wisdom."--Provided by publisher.